2002
DOI: 10.1080/00288330.2002.9517082
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect on lactate dehydrogenase and citrate synthase in snapper (Pagrus auratus)

Abstract: The activities of two enzymes involved in metabolic energy production, lactate dehydrogenase (LDH) and citrate synthase (CS), were determined in the white trunk musculature of snapper, Pagrus auratus (Bloch & Schneider 1801), to determine whether the metabolic capacity reflects seasonal variations. LDH and CS activities for a population of wild fish were monitored on a monthly basis over a period of 1 year and correlated with body length and seasonal variation. Significant correlations were observed between en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…Increases in aerobic capacity in poikilothermic vertebrates have been noted after 2–3 months of thermal acclimation and at increasingly lower temperatures than those we exposed the subtropical Mexican cavefish to (Johnston & Lucking, 1978), which are likely significant contributing factors towards why we did not see an effect of lower temperature acclimation in CS activity. LDH has often not shown a pattern relating to thermal seasonal variation, however (Majed et al, 2002), similar to our findings here.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Increases in aerobic capacity in poikilothermic vertebrates have been noted after 2–3 months of thermal acclimation and at increasingly lower temperatures than those we exposed the subtropical Mexican cavefish to (Johnston & Lucking, 1978), which are likely significant contributing factors towards why we did not see an effect of lower temperature acclimation in CS activity. LDH has often not shown a pattern relating to thermal seasonal variation, however (Majed et al, 2002), similar to our findings here.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, although the cave and surface morphs of Astyanax mexicanus utilized in this study evolved in distinct environmental habitats, they were bred and reared in a controlled laboratory environment, and hence the differences reported herein reflect evolutionary strategies and not short‐term responses to the local environment. Others have found that increased LDH activity may suggest energy demand changes to support anaerobic burst swimming (Majed et al, 2002), suggesting that the increases in lactate we see in cave morphotypes may be functionally associated with burst swimming. Notably, however, cave morphs of Astyanax mexicanus have substantially lower burst speed and their swimming pattern relies predominantly on slow gliding movements rather than more sustained active swimming exhibited in the surface morph, though they are capable of elevating muscle activity under stimulation (Olson et al, 2023).…”
Section: Discussionmentioning
confidence: 60%
“…Citrate synthase (CS) activity was assayed according to Majed et al (2002). The extraction buffer for CS was adjusted to a final pH of 8.0 at 20°C.…”
Section: Methodsmentioning
confidence: 99%